2015
DOI: 10.1111/jfb.12659
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between European eelAnguilla anguillainfection with non‐native parasites and swimming behaviour on encountering accelerating flow

Abstract: The effect of Anguillicola crassus, Pseudodactylogyrus bini and Pseudodactylogyrus anguillae infection on the behaviour of downstream migrating adult European eels Anguilla anguilla as they encountered accelerating water velocity, common at engineered structures where flow is constricted (e.g. weirs and bypass systems), was evaluated in an experimental flume. The probability of reacting to, and rejecting, the velocity gradient was positively related to A. crassus larval, adult and total abundance. High abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
(125 reference statements)
0
22
0
1
Order By: Relevance
“…However, increased stress and mortality have been reported in parasitized European eels that experienced periods of hypoxia (Gollock, Kennedy, & Brown, 2005;Lefebvre, Contournet, & Crivelli, 2007;Molnár, Székely, & Baska, 1991), indicating a cumulative negative effect from multiple stressors. Natural and experimental A. crassus infections impair swim bladder function (Würtz, Taraschewski, & Pelster, 1996), and laboratory swimming trials indicated that natural infections increase energy consumption and alter swimming behavior of the European eel and may thus interfere with the spawning migration and reproduction (Newbold et al, 2015;Palstra, Heppener, Ginneken, Székely, & Thillart, 2007;Pelster, 2015;Würtz et al, 1996). For the Japanese eel, body condition was not affected by A. crassus infections (Han et al, 2008).…”
mentioning
confidence: 99%
“…However, increased stress and mortality have been reported in parasitized European eels that experienced periods of hypoxia (Gollock, Kennedy, & Brown, 2005;Lefebvre, Contournet, & Crivelli, 2007;Molnár, Székely, & Baska, 1991), indicating a cumulative negative effect from multiple stressors. Natural and experimental A. crassus infections impair swim bladder function (Würtz, Taraschewski, & Pelster, 1996), and laboratory swimming trials indicated that natural infections increase energy consumption and alter swimming behavior of the European eel and may thus interfere with the spawning migration and reproduction (Newbold et al, 2015;Palstra, Heppener, Ginneken, Székely, & Thillart, 2007;Pelster, 2015;Würtz et al, 1996). For the Japanese eel, body condition was not affected by A. crassus infections (Han et al, 2008).…”
mentioning
confidence: 99%
“…Some authors have identified water temperature thresholds below which little or no migratory activity takes place (Euston et al, ); prolonged delays would result in silver eels encountering cooler temperatures and reduced day length, with the likelihood of delaying migration for a season. Parasite loading can also cause delays to downstream migration (Newbold et al, ). Prolonged delays can lead to reversion to yellow‐eel status and this has been recorded in silver A. anguilla in which seaward migration had been arrested (Durif et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Infected eels commonly suffer from impaired swim bladder functioning (Würtz et al 1996;Würtz and Taraschewski 2000) and reduced swimming abilities (Palstra et al 2007;Newbold et al 2015), likely affecting the spawning migration (Pelster 2015). As a result, the parasite might have a strong effect on the viability of the European eel and variability at Electronic supplementary material The online version of this article (doi:10.1007/s12686-015-0501-z) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%